Financial Performance Assessment of A Bank: An Analysis of Financial Ratio at PT Bank Pembangunan Daerah Papua Period 2018-2022 - Murib, Pendison; Susanto, Heri; Wahidhani, Eha Hasni (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to analyze financial ratios to assess the financial performance of PT Pembangunan Daerah Papua for the 2018-2022 period. The research method is quantitative analysis with liquidity ratios, solvency ratios and profitability ratios, with the data used in this research being secondary data obtained from the company's official website. The results of this research reveal that the liquidity ratio results do not meet financial performance standards, while the company's solvency ratio and profitability ratio meet standards, although overall financial performance is still below the banking industry average.